A lower body height and wider foot stance are positively associated with the generation of individual scrummaging forces in rugby - Green, A.; Kerr, S.; Dafkin, C.; Olivier, B.; McKinon, W. (International Journal of Performance Analysis in Sport, 2017)
A scrum is a contest to win possession of the rugby ball. The current study investigated potential kinematic parameters related to individual scrummaging force production. Twenty-five "tight-five" players (body mass: 103.0 ± 12.1 kg; height: 1.85 ± .09 m) individually scrummaged against an instrumented ergometer, while body kinematics were captured. Pearson`s correlations between force generation and kinematics of individual scrummaging performances were performed. Body mass was correlated to the engagement (r = .641), peak (r = .531) and sustained (r = .438) forces. Stance width was significantly correlated with the individual scrummaging forces at engagement (r = .422) and sustained phases (r = .540) but not at peak phase (r = .369). Higher scrummaging forces were achieved at lower pelvic and back heights. The only significant relationship during the start-sustained phase was the change in pelvic height (r = -.562). Changes in right hip (r = -.477) and right knee (r = .474) angles were correlated to the change in force during engagement-peak phase. During engagement-sustained phases, change in force magnitude was correlated to changes in pelvic height (r = -.585), left hip (r = .549) and right ankle (r = .657). The change in pelvic height (r = -.518) was the only correlate during the peak-sustained phase. The presented data highlight the role of a lower body height and wider stance in the attainment of greater individual scrummaging force.